2015
DOI: 10.1185/03007995.2015.1094653
|View full text |Cite
|
Sign up to set email alerts
|

Optimum treatment strategies for polyallergic patients – analysis of a large observational trial

Abstract: After 1 year of treatment, polyallergic patients responded similarly to the five-grass pollen tablet as monoallergic patients. For polyallergic patients in whom additional treatment was needed, a second SLIT may be more beneficial than a SCIT or symptomatic co-medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…None were life-threatening or required the use of epinephrine. The majority of SADRs (30, occurring in six patients) were reported during the first study year, and these have been described previously [21]. Three SADRs occurred in the second study year, all on day 6 in the same patient (a 27-year-old man): pharyngeal edema, throat irritation and sneezing.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…None were life-threatening or required the use of epinephrine. The majority of SADRs (30, occurring in six patients) were reported during the first study year, and these have been described previously [21]. Three SADRs occurred in the second study year, all on day 6 in the same patient (a 27-year-old man): pharyngeal edema, throat irritation and sneezing.…”
Section: Resultsmentioning
confidence: 58%
“…The majority (93.1%) of these ADRs occurred during the first study year [21]. The most frequent ADRs were local reactions at the application site, particularly throat irritation, mouth edema and oral paresthesia (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decision for monoallergen vs polyallergen immunotherapy differs by provider and practice region . Several prospective, randomized trials have demonstrated efficacy of both monoallergen and polyallergen immunotherapy for the treatment of polyallergy patients. With the increase in availability of U.S. Food and Drug Administration (FDA)‐approved sublingual immunotherapies, the decision for allergen selection in the setting of polysensitization is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that SLIT approximately halved the symptom-medication scores compared to the score registered in drug-treated patients. Since then, several real-life studies were performed, including 11 studies on SCIT (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), 15 on SLIT (6,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and 5 on both (30-…”
Section: Real-life Studies On Aitmentioning
confidence: 99%